ANALISIS GAYA KEPEMIMPINAN DAN MODEL KOMUNIKASI DI PERPUSTAKAAN PUSAT UIN SUMATERA UTARA - Habiburrahman (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Leaders with their leadership style can influence employees to improve performance at work and able to create a climate of communication that can affect employee productivity. This study aims to describe the leadership style and communication model applied at the Central Library of UIN Sumatra Utara Medan. In this study, the authors used a qualitative method with a descriptive-analytic approach. The data collected is the result of observation, interviews and literature studies. From this study it can be seen that the head of the librarian as the leader of the North Sumatra UIN Library involves subordinates in making decisions, the head of the librarian is willing to accept suggestions and involve subordinates in decision making which is a characteristic of a democratic leadership style and the communication that is carried out is in the form of interactive communication and flows upward and down. This means that the process of conveying messages from the head of the librarian to subordinates and vice versa is accompanied by a direct response.